Three years' clinical practice of Radium-223 therapy in patients with symptomatic bone metastases from metastatic castrate-resistant prostate cancer: a single-centre experience. Issue 4 (April 2020) - Gazzilli, Maria; Durmo, Rexhep; Cossalter, Erika; Cerudelli, Elisabetta; Panarotto, Maria Beatrice; Albano, Domenico; Bertagna, Francesco; Giubbini, Raffaele
Abstract : Background: Radium-223 was a treatment approved for patients with metastatic castrate-resistant prostate cancer, symptomatic bone metastases and no-visceral metastases, in progression after at least two prior lines of systemic therapy, or ineligible for any available systemic treatment. The aim of this study was to provide further characterization and sub-selection of patients who would benefit most with Radium-223 treatment. Methods: We retrospectively analysed 38 patients treated with Radium-223 between 2015 and 2018. All patients underwent a baseline visit and a bone scintigraphy. Bone scan, ALP and PSA levels were repeated after third and after the end of therapy. All patients were re-evaluated after 2 months from the end of therapy. Survival curves were plotted according to the Kaplan–Meier method and differences between groups were analysed by using a two-tailed log-rank test. Results: The response to the treatment in term of change in pain was reduction in 16 patients; no change in 14 and increased in eight. We arbitrarily established a cut-off 10 bone lesions to evaluate the response: patients with less than 10 metastasis had significant differences in PFS (P < 0.001) compared to patients with more than 10, no statistical significance was found considering the OS (P = 0.23) between the two groups. The same results were founded in patients with baseline ALP <220 U/L with a PFS (P < 0.001) and OS (P = 0.027). Conclusion: The most important finding was the correlation between the number of bone metastasis and ALP with outcome survival and efficacy of Radium-223 treatment.